Physical attributes and limiting water range as soil quality indicators after mechanical harvesting of sugarcane - Filho, Oswaldo Julio Vischi; de Souza, Zigomar Menezes; de Souza, Gustavo Soares; da Silva, Reginaldo Barbosa [UNESP]; Torres, José Luiz Rodrigues; de Lima, Márcio Emanuel; Tavares, Rose Luiza Moraes (Southern Cross Publishing, 2017)
Monitoring soil physical quality in areas cultivated with sugarcane has become a key management practice of this crop. It is due to the in-field traffic of heavy machines, implements, high mass harvesters and transhipments in the area have caused changes in soil structure and promoted the fall of the crop yield.. This study evaluated physical attributes of soil and the least limiting water range to assess the effects caused by wheel traffic in areas with mechanized harvest of sugarcane. The design was completely randomized in a factorial 2 x 2 x 4, which were evaluated two areas of mechanical harvesting: 1 - Six years (T1); 2 - Eighteen years of cultivation (T2); Two sampling sites: 1 - Canteiro; 2 - Planting line; Four layers of soil sampled (0.00 to 0.10, 0.10-0.20, 0.20-0.30 and 0.30-0.40 m) with 4 repetitions. We evaluated bulk density (BD), mechanical resistance to penetration (RP), water content in the soil (WCS), macroporosity (Ma), microporosity (Mi), total porosity (TP), water retention curve, the least limiting water range (LLWR) and soil organic carbon (SOC). We observed that the area with mechanical harvest system after three crop cycles produced a high load-bearing capacity and high SOC. The same area also demonstrated high Ma and LLWR, and low BD and RP levels in the rows. The LLWR levels were high as well in the area with one cane cycle but decreased as the number of harvest cycles increased. In the areas with one and three cycles the critical bulk density (CBD) ranged between 1.40-1.50 Mg m-3 and 1.24-1.28 Mg m-3 respectively, while the LLWR was zero (LLWR = 0) with the limiting RP between 2.0 and 3.5 Mpa. The physical attributes are changed by heavy machinery traffic in the cane fields, but the effects of these changes are minimized when several crop cycles are conducted in the same area.
Keywords: Compaction; Mechanization; Soil porosity; The least limiting water range